Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
[ "article:topic", "license:ccbyncsa", "showtoc:no", "authorname:wtrench" ]
Mathematics LibreTexts

7.4E: Regular Singular Points Euler Equations (Exercises)

  • Page ID
    18314
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

    \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

    In Exercises [exer:7.4.1} –[exer:7.4.18} find the general solution of the given Euler equation on \((0,\infty)\).

    [exer:7.4.1] \(x^2y''+7xy'+8y=0\)

    [exer:7.4.2] \(x^2y''-7xy'+7y=0\)

    [exer:7.4.3] \(x^2y''-xy'+y=0\)

    [exer:7.4.4] \(x^2y''+5xy'+4y=0\)

    [exer:7.4.5] \(x^2y''+xy'+y=0\)

    [exer:7.4.6] \(x^2y''-3xy'+13y=0\)

    [exer:7.4.7] \(x^2y''+3xy'-3y=0\)

    [exer:7.4.8] \(12x^2y''-5xy''+6y=0\)

    [exer:7.4.9] \(4x^2y''+8xy'+y=0\)

    [exer:7.4.10] \(3x^2y''-xy'+y=0\)

    [exer:7.4.11] \(2x^2y''-3xy'+2y=0\)

    [exer:7.4.12] \(x^2y''+3xy'+5y=0\)

    [exer:7.4.13] \(9x^2y''+15xy'+y=0\)

    [exer:7.4.14] \(x^2y''-xy'+10y=0\)

    [exer:7.4.15] \(x^2y''-6y=0\)

    [exer:7.4.16] \(2x^2y''+3xy'-y=0\)

    [exer:7.4.17] \(x^2y''-3xy'+4y=0\)

    [exer:7.4.18] \(2x^2y''+10xy'+9y=0\)

    [exer:7.4.19]

    Adapt the proof of Theorem [thmtype:7.4.3} to show that \(y=y(x)\) satisfies the Euler equation

    \[\label{eq:7.4.{exer:7.4.19}A} ax^2y''+bxy'+cy=0\nonumber\]

    on \((-\infty,0)\) if and only if \(Y(t)=y(-e^t)\)

    \[a {d^2Y\over dt^2}+(b-a){dY\over dt}+cY=0.\nonumber\]

    on \((-\infty,\infty)\).

    Use (a) to show that the general solution of Equation \ref{eq:7.4.{exer:7.4.19}A} on \((-\infty,0)\) is

    \[\begin{aligned} y&=&c_1|x|^{r_1}+c_2|x|^{r_2}\mbox{ if $r_1$ and $r_2$ are distinct real numbers; } \\ y&=&|x|^{r_1}(c_1+c_2\ln|x|)\mbox{ if $r_1=r_2$; } \\ y&=&|x|^{\lambda}\left[c_1\cos\left(\omega\ln|x|\right)+ c_2\sin\left(\omega\ln|x| \right)\right]\mbox{ if $r_1,r_2=\lambda\pm i\omega$ with $\omega>0$}.\end{aligned}\nonumber\]

    [exer:7.4.20] Use reduction of order to show that if

    \[ar(r-1)+br+c=0\nonumber\]

    has a repeated root \(r_1\) then \(y=x^{r_1}(c_1+c_2\ln x)\) is the general solution of

    \[ax^2y''+bxy'+cy=0\nonumber\]

    on \((0,\infty)\).

    [exer:7.4.21] A nontrivial solution of

    \[P_0(x)y''+P_1(x)y'+P_2(x)y=0\nonumber\]

    is said to be oscillatory on an interval \((a,b)\) if it has infinitely many zeros on \((a,b)\). Otherwise \(y\) is said to be nonoscillatory on \((a,b)\). Show that the equation

    \[x^2y''+ky=0 \quad (k=\; \mbox{constant})\nonumber\]

    has oscillatory solutions on \((0,\infty)\) if and only if \(k>1/4\).

    [exer:7.4.22] In Example

    Example \(\PageIndex{1}\):

    Add text here. For the automatic number to work, you need to add the “AutoNum” template (preferably at7.4.2} we saw that \(x_0=1\) and \(x_0=-1\) are regular singular points of Legendre’s equation

    \[(1-x^2)y''-2xy'+\alpha(\alpha+1)y=0. \tag{A}\]

    Introduce the new variables \(t=x-1\) and \(Y(t)=y(t+1)\), and show that \(y\) is a solution of (A) if and only if \(Y\) is a solution of

    \[t(2+t){d^2Y\over dt^2}+2(1+t){dY\over dt}-\alpha(\alpha+1)Y=0,\nonumber\]

    which has a regular singular point at \(t_0=0\).

    Introduce the new variables \(t=x+1\) and \(Y(t)=y(t-1)\), and show that \(y\) is a solution of (A) if and only if \(Y\) is a solution of

    \[t(2-t){d^2Y\over dt^2}+2(1-t){dY\over dt}+\alpha(\alpha+1)Y=0,\nonumber\]

    which has a regular singular point at \(t_0=0\).

    [exer:7.4.23] Let \(P_0,P_1\), and \(P_2\) be polynomials with no common factor, and suppose \(x_0\ne0\) is a singular point of

    \[P_0(x)y''+P_1(x)y'+P_2(x)y=0. \tag{A}\]

    Let \(t=x-x_0\) and \(Y(t)=y(t+x_0)\).

    Show that \(y\) is a solution of (A) if and only if \(Y\) is a solution of

    \[R_0(t){d^2Y\over dt^2}+R_1(t){dY\over dt}+R_2(t)Y=0. \tag{B}]

    where

    \[R_i(t)=P_i(t+x_0),\quad i=0,1,2.\nonumber\]

    Show that \(R_0\), \(R_1\), and \(R_2\) are polynomials in \(t\) with no common factors, and \(R_0(0)=0\); thus, \(t_0=0\) is a singular point of (B).